The Usability of Yoga in Voice Training: An Experimental Study Based on Performance - Ertek Babaç, Ezgi; Köse, H. Seval; Baş Aslan, Ummuhan (Journal of History Culture and Art Research, 2021)
The aim of this research is to investigate whether yoga, which is an important approach in the relaxation of body and mind and one of the oldest known relaxation methods; its practices including posture, breathing and meditation, makes any difference in students’ performance in vocal education. As a method, experimental research, which is an important type of quantitive research, and a pre-test post-test control group design, which is a design of it, were used. The study group of the research consisted of 18 students (9 experiments-9 controls) determined by random assignment method among the first-grade students who took the vocal education class in the Department of Music Education of Burdur Mehmet Akif Ersoy University in the 2019-2020 academic year. The data in the study were collected through the "Individual Voice Training Performance Scale" which was developed by Ertek Babaç and Dalkıran (2019). After having yoga instructor training course by the researcher, the students in the experimental group were practiced Hatha Yoga posture, breathing and meditation practices for 1,5 hours a week for 10 weeks. It had been investigated whether there was a significant difference between the vocal performance of the students who had not started yoga practices yet and their vocal performances at the end of the yoga practices that had been in coordination with vocal training lessons for 10 weeks. The changes of the students in the control group, who did not participate in yoga practice but took part in the vocal training course only, were also measured at the end of 10 weeks. Besides, it was investigated whether there was any difference between the students of the experimental group who practiced yoga and the students of the control group who did not. In the conclusion section of the study, it was stated that yoga contributed to the performance of students in the experimental group and to all of the target behaviors that were discussed as sub-problems. In comparison between the experimental and the control groups, a significant difference was detected in all target behaviors except for the target behaviors of performing the work with correct articulation and diction and performing the work with the correct notation. It has been concluded that yoga supports the development of performance skills of the students in vocal training in overall performance.